Hourly rainfall distribution in east Malaysia during the southwest monsoon season - Camerlengo, Alejandro L. (2000)
The hourly rainfall pattern during the southwest (SW) monsoon season is addressed. For this purpose, hourly rainfall data of nine selectedstations are analyzed. The study period was thirtyone years. The results of this investigation show that four main mechanisms are responsible for the daily rainfall distribution in East Malaysia. . These mechanisms are: (a) convergence of land breezes, (b) increase of the atmospheric lapse rate during the night, (c) convection and (d) sea breeze. For example, these four mechanisms may be important in a particular station in a given month and not in the following one or the precedent one. Or it may just be that one mechanism is important for a different station in a given month.